Wilhelm Dilthey's Thoughts on Understanding, Hermeneutics and Communication - Financy, Fendy; Fitzerald Kennedy Sitorus (Asian Journal of Philosophy and Religion, 2024)
Wilhelm Dilthey, a towering figure in the realm of philosophy, dedicated his life's work to unravelling the complexities of human experience. Dilthey believed that life is not merely a series of random events, but a tapestry woven from these experiences, which collectively influence our perspectives and sense of being. By examining Dilthey's thoughts on communication as a process of shared knowledge and meaning making, we gain valuable insights into how we bridge the gap between different perspectives and forge deeper connections. Through a quantitative approach and literature review Dilthey's perspectives are analyzed. Dilthey believed a text goes beyond its literal meaning; it symbolizes deeper significance. Understanding the true depth of a symbol requires venturing beyond its surface meaning and delving into its historical context. Symbols are not merely arbitrary signs; they are often imbued with layers of meaning accumulated over time. These layers reflect the cultural, social, and political landscapes from which the symbol emerged. To fully grasp the symbolic meaning, then, requires an exploration of its historical journey.  Despite the occasional inclusion of natural science objects in humanities, Dilthey saw a clear distinction between the two. He saw understanding as a process of grasping the intended meaning rooted in life experiences. Therefore, Dilthey's concept of meaning is historical highlighting the significance of personal and collective life experiences in interpretation.